Bosbefok: Constructed images and the memory of the South African 'border war ' - Doherty, C M W (My University, 2014)
This thesis is part of a creative arts PhD which explores the possibilities of constructed images and the memory of the South African Border War. It was presented together with an exhibition of constructed photographic images entitled BOS. In the thesis I argue that the memory of the war, an event now almost three decades past, continues to be problematic. I also argue that photographs are themselves complex and constructed objects that do not provide a simple truth about either history or memory. Photographs can supplement or support memories but they are always to be viewed with suspicion. In Chapter One I explore the limitations imposed on the speech of conscripts, both during the conflict and in the years following the conclusion of hostilities. In Chapter Two I examine the recent appearance of several ‘anti heroic’ memoirs of the conflict written by conscripts. The use of the medical diagnosis of post-traumatic stress syndrome (PTSD) in these writings is critically examined. Chapter Three focuses on a development in the ideas of the two most influential figures in the field of Anglophone photographic theory, Susan Sontag and Roland Barthes. I argue that their initial hostility to the photographic image on ethical/political grounds has been replaced by a more nuanced engagement with the power of the image. I then examine the views of two contemporary writers on photography, both deeply involved with the analysis of traumatic images: Ariella Azoulay and Susie Linfield. In Chapter Four, I engage with the artistic practice of the American photographer, David Levinthal, an important reference point for this project because of his photographic work with miniatures and toys and his place within what I describe as ‘critical postmodernism’. In Chapter Five, I examine the themes of silence and censorship as these pertain to the photography of the Border War using Susan Sontag’s notion of the “ecology of images”. I analyze the types of images which have been produced from the war, looking at the “limited photojournalism” of John Liebenberg and the role of iconic images in the propaganda war. Finally, in Chapter Six, I present an account of the process of creating the work for the BOS exhibition in which I employed a combination of strategies involving appropriation, miniaturization, and re-staging
Keywords: Psychoanalysis and the arts.; Post-traumatic stress disorder.